2018
DOI: 10.1159/000489563
|View full text |Cite
|
Sign up to set email alerts
|

Use of Gene Expression Analysis for Discrimination of Primary and Secondary Adenocarcinoma of the Liver

Abstract: Background: Due to late diagnosis and resistance to chemotherapy, most patients with cholangiocarcinoma have an unfavorable prognosis. Despite the use of immunohistochemistry (IHC) in clinical routine, differentiation between intrahepatic cholangiocarcinoma (ICC) and secondary adenocarcinomas of the liver is frequently not clear, leading to false diagnosis and treatment decisions. Methods: Oligonucleotide microarrays (Affymetrix Hu133A©) were used for gene expression analysis of ICC (n = 11) and sec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 38 publications
(39 reference statements)
0
5
0
Order By: Relevance
“…By analyzing the correlation between gene expression and clinical characteristics in patients with malignant solid tumors, the expression of BCL11A was significantly confirmed to be positively correlated with some tumor metastases, such as breast cancer [ 20 ], liver cancer [ 21 ], laryngeal squamous cell carcinoma [ 22 ], lung squamous cell carcinoma [ 23 ], and so on. Studies found that BCL11A could participate in epithelial-mesenchymal transition and promote breast cancer metastasis by the Wnt/β-catenin signaling pathway [ 8 ].…”
Section: Discussionmentioning
confidence: 99%
“…By analyzing the correlation between gene expression and clinical characteristics in patients with malignant solid tumors, the expression of BCL11A was significantly confirmed to be positively correlated with some tumor metastases, such as breast cancer [ 20 ], liver cancer [ 21 ], laryngeal squamous cell carcinoma [ 22 ], lung squamous cell carcinoma [ 23 ], and so on. Studies found that BCL11A could participate in epithelial-mesenchymal transition and promote breast cancer metastasis by the Wnt/β-catenin signaling pathway [ 8 ].…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, careful analysis of immunostaining for CK7 and CK20 is necessary, with consideration of all clinical information, while acknowledging that no tumor demonstrates absolute consistency in its staining with these markers. Hass and colleagues utilized oligonucleotide arrays to differentiate and identify potential biomarkers of intrahepatic cholangiocarcinoma (ICC) and colorectal metastases ( 86 ). Through microarray analysis, numerous dysregulated genes were identified in ICC, with KRT7 being overexpressed in over 80% of ICC cases.…”
Section: Differentiate Diagnosis Of Cancers Via Krt7mentioning
confidence: 99%
“…Through microarray analysis, numerous dysregulated genes were identified in ICC, with KRT7 being overexpressed in over 80% of ICC cases. Interestingly, KRT7 was significantly downregulated in the analyzed tumor probes from metastatic adenocarcinomas, emphasizing the importance of KRT7 in distinguishing primary from metastatic adenocarcinomas of the liver in clinical practice (86). Roy et al aimed to differentiate primary bladder adenocarcinoma (PBA) from metastatic colon adenocarcinoma (MCA), a challenging diagnostic and clinical issue (87).…”
Section: Differentiate Diagnosis Of Cancers Via Krt7mentioning
confidence: 99%
“…In an approach to identify biomarkers for disease and therapy responses using gene expression arrays, Cripto was one of the markers specifically associated with the metastasis stage, thus discriminating primary intrahepatic cholangiocarcinoma from secondary metastasis [114]. Cripto may also be beneficial as a biomarker to discriminate among diseases that have different treatment approaches.…”
Section: Cripto In Experimental Medical Research: Therapeutic and Tramentioning
confidence: 99%